2016
DOI: 10.1515/johh-2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

A regional comparative analysis of empirical and theoretical flood peak-volume relationships

Abstract: This paper analyses the bivariate relationship between flood peaks and corresponding flood event volumes modelled by empirical and theoretical copulas in a regional context, with a focus on flood generation processes in general, the regional differentiation of these and the effect of the sample size on reliable discrimination among models. A total of 72 catchments in North-West of Austria are analysed for the period . From the hourly runoff data set, 25 697 flood events were isolated and assigned to one of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Gaál et al (2012Gaál et al ( , 2015 and Szolgay et al (2016) found similar results when they 20 analyzed durations of flood events across Austria. They found that the flood event duration consistently increases with increasing snow-to-rainfall ratio of the process leading to the event despite the diversity of the non-climate catchment characteristics that have impact on the flood generation process that affect the flood event duration.…”
Section: Discussionmentioning
confidence: 65%
“…Gaál et al (2012Gaál et al ( , 2015 and Szolgay et al (2016) found similar results when they 20 analyzed durations of flood events across Austria. They found that the flood event duration consistently increases with increasing snow-to-rainfall ratio of the process leading to the event despite the diversity of the non-climate catchment characteristics that have impact on the flood generation process that affect the flood event duration.…”
Section: Discussionmentioning
confidence: 65%
“…where F Q f ;Q s q f ; q s is the joint CDF of fast flow and slow flow; F Q f q f is the CDF of fast flow; F Q s q s ð Þ is the CDF of slow flow; and C is a copula function which quantifies the joint CDF of fast flow and slow flow as a function of F Q f q f and F Q s q s ð Þ. Copulas have been applied for characterizing complex hydrological events such as floods through a small number of dependent variables such as flood peak, volume, and duration (Favre et al, 2004;Grimaldi & Serinaldi, 2006;Salvadori & De Michele, 2004;Szolgay et al, 2016;Zhang & Singh, 2007). Kao and Govindaraju (2008) applied a trivariate copula to characterize the temporal distribution of extreme rainfall.…”
Section: Quantifying the Dependence Of Fast And Slow Flows Using Copulamentioning
confidence: 99%
“…Volpi and Fiori [2] used Gumbel-Hougaard copulas to model dependency between peak and volume in flood analysis; Gräler et al [1] used synthetic dataset to show difference in performance of 2D and 3D copulas for various combinations of hydrologic variables; Xu et al [5] compared four Archimedean family copulas for derivation of a design flood hydrograph; Bender et al [14] used Gumbel copula for bivariate analysis of concurrent flows at a river confluence, and Bender et al [15] continued to investigate bivariate analysis of discharges on confluences, investigating sites where floods do not occur simultaneously. Szolgay et al [16] evaluated applicability of different copula types to a peakvolume flood relationship over a large region in Austria and its sub-catchments, and also studied the influence of the data series length on bivariate copula performance. Sraj et al [17] compared three copula families for bivariate flood frequency analysis in the Sava River basin in Slovenia, and the results obtained by Ozga-Zielinski et al [18] showed that the Gumbel-Hougaard copula yields better results compared to Gaussian copula for snowmelt floods.…”
Section: Theoretical Backgroundmentioning
confidence: 99%